2008
DOI: 10.1111/j.1600-0714.2008.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16 in oral cancer and premalignant lesions

Abstract: As a marker, p16 is not reliable for oral mucosal dysplasia and malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 35 publications
4
42
0
1
Order By: Relevance
“…p16 Ink4a expression has been evaluated in several tumor types with very different results, ranging from its loss or downregulation (Brambilla et al, 1999a, b;Schneider-Stock et al, 2005;Ayhan et al, 2010) to its clear overexpression (Milde-Langosch et al, 2001;Armes et al, 2005;Zhao et al, 2006;Angiero et al, 2008;Buajeeb et al, 2009). The main objective of this review is to clarify these apparently contrasting expression patterns and to reveal their implications in cancer management.…”
Section: Introductionmentioning
confidence: 99%
“…p16 Ink4a expression has been evaluated in several tumor types with very different results, ranging from its loss or downregulation (Brambilla et al, 1999a, b;Schneider-Stock et al, 2005;Ayhan et al, 2010) to its clear overexpression (Milde-Langosch et al, 2001;Armes et al, 2005;Zhao et al, 2006;Angiero et al, 2008;Buajeeb et al, 2009). The main objective of this review is to clarify these apparently contrasting expression patterns and to reveal their implications in cancer management.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of p16 in HNSCC has also been shown [20,21]. This is still debated as other studies have proposed that there is a reduction in p16 expression [22,23]. …”
Section: Discussionmentioning
confidence: 86%
“…Nuclear p16 expression has been described in adult but not fetal tissues in many organs (5) and in cells in culture reaching their limit of population doubling (15). Buajeeb et al (16) have reported that p16 is not reliable for oral mucosal dysplasia and malignant transformation, although it is possible that p16 plays a role in cell senescence in normal oral mucosa since the protein is detectable by Western blotting in normal oral mucosa (3). Sousa et al (17) have reported that no significant statistical difference of the cell proliferation rate between oral lichen planus and epithelial dysplasia (p>0.05) and between the epithelial dysplasia and oral squamous cell carcinoma (p>0.05) was observed.…”
Section: Discussionmentioning
confidence: 99%